J/Ψ (1S) and Ψ (2S) Production in p-p Collisions at E=5.44 TeV - Leonard S Kisslinger (Annals of Mathematics and Physics - Peertechz Publications, 2023)
I estimate the differential rapidity cross sections for J/Ψ and Ψ (2S) via pp (proton-proton) collisions at E=510 GeV. The J/Ψ  is a standard charm quark and anti-charm quark, c and  while Ψ (2S) is a mixed hybrid c meson. For the Ψ (2S) I use the mixed heavy quark hybrid theory, with states approximately 50% standard and 50% hybrid charmonium.